Diffraction contrast tomography for the study of polycrystalline stainless steel microstructures and stress corrosion cracking - King, A; Ludwig, W; Engelberg, D; Marrow, T (2011)
X-ray diffraction contrast tomography is a non-destructive technique for the 3D characterisation of polycrystalline microstructures containing up to a few 1000 grains. The sample is illuminated with a monochromatic beam of high energy synchrotron radiation. As the sample is rotated, and as grains pass through alignments for Bragg diffraction, diffraction spots are recorded on a 2D detector placed close behind the sample. The diffraction geometry is used to assign spots to the grains from which they arise, and to determine the crystallographic orientations of grains. The spots are used as projections of the grains to reconstruct the grain shapes. The technique has been applied to several materials science investigations in stainless steels, including the 3D characterisation of grain boundary networks, and in-situ studies of intergranular stress corrosion cracking. © 2011 EDP Sciences.